Implementing bioburden reduction and control on the deliquescent hydrogel of the HABIT/ExoMars 2022 instrument. (August 2020) - Mathanlal, Thasshwin; Nazarious, Miracle Israel; Ramachandran, Abhilash Vakkada; Zorzano, Maria-Paz; Martin-Torres, Javier; Rettberg, Petra
Abstract: The HabitAbility: Brines, Irradiation and Temperature (HABIT) instrument will be part of the ExoMars 2022 mission (ESA/Roscosmos) and will be the first European In-situ Resource Utilization (ISRU) instrument capable of producing liquid water on Mars. HABIT is composed by two modules: Environmental Package (EnvPack) and Brine Observation Transition To Liquid Experiment (BOTTLE). EnvPack will help to study the current habitability conditions on Mars investigating the air and surface thermal ranges and Ultraviolet (UV) irradiance; and BOTTLE is a container with four independent vessels housing deliquescent salts, which are known to be present on Mars, where the liquid water will be produced after deliquescence. In order to prevent capillarity of deliquescent or hydrated salts, a mixture of deliquescent salts with Super Absorbent Polymer (SAP) based on polyacrylamide is utilized. This mixture has deliquescent and hydrogel properties and can be reused by applying a thermal cycle, complying thus with the purpose of the instrument. A High Efficiency Particulate Air (HEPA) grade filter made of polytetrafluroethylene (PTFE) porous membrane sandwiched between spunbounded non-woven fabric stands as a physical barrier allowing interaction between the gaseous molecules of the Martian atmosphere and the salt mixtures, and at the same time preventing the passage of any potential biological contamination from the cells to the outside or vice-versa. In addition to the physical barrier, a strict bioburden reduction and analysis procedure is applied to the hardware and the contained salt mixtures adhering to the European Cooperation for Space Standardization protocol of microbial examination of flight hardware (ECSS-Q-ST-70-55C). The deliquescent salts and the SAP products need to be properly treated independently to adhere to the planetary protection protocols. In this manuscript, we describe the bioburden reduction process utilized to sterilize the salt mixtures in BOTTLE and the assays adopted to validate the sterilization. We also describe the construction of a low-cost, portable ISO 7 cleanroom tent, exclusively designed for planetary protection tests. The sterilization process involves Dry Heat Microbial Reduction (DHMR) of the deliquescent salts and the SAP mixtures. The performance of SAP after DHMR is validated to ensure its working efficiency after sterilization. A slightly modified version of the standard swab assay is used in the validation process and a comparison is made between samples exposed to a thermal shock treatment and those without thermal shock, to determine the best assay to be applied for future space hardware utilizing such salt mixtures for planetary investigation and In-Situ Resource Utilization (ISRU). The demonstration of the compatibility of these products with the processes commonly required for space applications has implications for the future exploration of Mars. Highlights: HABIT deliquescent hydrogel meets COSPAR Planetary Protection standard, category IVb. Deliquescent hydrogel constitute a mixture of salts and Super Absorbent Polymer (SAP). A modified standard swab assay procedure is followed for bioburden assay validation. DHMR of the deliquescent hydrogel results in no colony forming units (CFU). An ISO 7 low cost portable clean room tent has been designed for the bioburden tests.